Extended IgE profile based on an allergen macroarray: a novel tool for precision medicine in allergy diagnosis - Heffler, Enrico (World Allergy Organ J, 2018)
BACKGROUND: Precision medicine (PM) is changing the scope of allergy diagnosis and treatment. An in vitro IgE assay, a prototype PM method, was developed in the sixties and has garnered increasing interest because of the introduction of recombinant components in the test. More recently, microarrays of allergen components have significantly improved the ability to describe the IgE profile. Aim of this study was to evaluate the characteristics of the newly developed Allergy Explorer (ALEX), a macroarray containing both extracted “whole” allergens and molecular components. This method allows the acquisition of an IgE profile comprising 282 reagents (157 allergen extracts and 125 components), resulting in the widest screening of potential allergens available. METHODS: Sera from 43 patients with allergies were assayed with ALEX and then with ImmunoCAP ISAC. The results of the two tests were compared, and the consistency of the molecular results with the presence of IgE in the relevant extract was also evaluated. RESULTS: A good correlation between ISAC and ALEX was observed. The ALEX results for second-level tests (i.e., specific IgE to complete extracted allergens) were consistent with the results obtained for the relevant components. DISCUSSION: Despite differences in the methodology, the IgE profiles detected for molecular allergens by ALEX and ISAC were very similar. The differences were mainly related to the lower dynamic range of ALEX and to the use of a CCD inhibitor in the first incubation phase, which reduced the binding of IgE to CCD, as represented in the extracted allergens and components. CONCLUSION: Based on our findings, ALEX is a novel tool for describing the IgE profile in a PM setting, where the IgE assay must be performed on many allergens and components. In particular, polysensitized patients and patients with pollen-food syndrome will have a real advantage due the combination of the second and third levels of allergy diagnostics in the same chip.